PEKERJA SOSIAL FUNGSIONAL: KOMPETENSI DAN PERMASALAHANNYA (SUATU TELAAHAN TENTANG KINERJA PEKERJA SOSIAL FUNGSIONAL DALAM MELAKSANAKAN PEMBANGUNAN KESEJAHTERAAN SOSIAL DI INDONESIA) - Helly Ocktilia (Politeknik Kesejahteraan Sosial Bandung, 2013)
AbstractThe development of social welfare is a form to implementation of development in order to achieve quality of life of human being in Indonesia, particularly for the Client of Social Welfare Service. To implement of it, requires a reliable and powerful actors. One of them is the social work profession. In carrying out its role, functional social workers are required to have sufficient competence. This paper is intended to gain an overview of the functional social worker performance as well as competence and problems in implementing social welfare development. The method used in this paper is the literature study. The research results show that in performing basic tasks, functions and roles of functional social workers often collide with competence of social work that must be possessed. Educational background of functional social worker that non-profession social work, while on the other hand, the opportunities and the chance to develop themselves through education and training is relatively limited, raises a variety of internal and external problems that faced by functional social workers.Keywords: the development of social welfare, functional social worker, competence and social workers problems. Abstrak Pembangunan kesejahteraan sosial, merupakan wujud pelaksanaan pembangunan untuk mencapai kualitas hidup manusia Indonesia seutuhnya, khususnya Pemerlu Pelayanan Kesejahteraan Sosial (PPKS). Penyelenggarannya, memerlukan pelaku yang handal dan tangguh. Salah satunya adalah profesi pekerjaan sosial. Dalam melaksanakan peranannya, pekerja sosial fungsional dituntut untuk memiliki kompetensi yang memadai. Tulisan ini ditujukan untuk memperoleh gambaran tentang kinerja pekerja sosial fungsional serta kompetensi dan permasalahannya dalam melaksanakan pembangunan kesejahteraan sosial. Metode yang digunakan dalam penulisan adalah studi kepustakaan. Hasil penelusuran menunjukkan bahwa dalam melaksanakan tugas pokok, fungsi dan peranannya pekerja sosial fungsional seringkali berbenturan dengan kompetensi pekerjaan sosial yang harus dimilikinya. Latar belakang pendidikan pekerja sosial fungsional yang non profesi pekerjaan sosial, sementara di sisi lain peluang dan kesempatan untuk mengembangkan diri melalui pendidikan dan pelatihan relatif terbatas, memunculkan berbagai permasalahan internal dan eksternal yang dihadapi oleh pekerja sosial fungsional. Kata kunci: pembangunan kesejahteraan sosial, pekerja sosial fungsional, kompetensi dan permasalahan pekerja sosial